A Bioequivalence Study of the Cefuroxime Axetil in Healthy Volunteers - Rojanasthien N. (2014)
The bioequivalence of 250-mg cefuroxime axetil was evaluated; Furoxime® (by the Siam Bheasach Company, Thailand) as the test and Zinnat® (GlaxoWellcome) as the reference. The two products were administered as a single dose according to a two-way crossover design, 1-week washout period to 12 healthy Thai male volunteers. Thereafter, serial blood samples were collected over a period of 15 hours. Plasma cefuroxime concentrations were measured by HPLC. The pharmacokinetic parameters were analyzed by noncompartmental analysis. RESULTS: The Tmax [median (range, h)] of Furoxime® and Zinnat® were 1.5 (1.0-3.0) and 1.75 (1.0-3.5), respectively. The Tmax of Furoxime® was faster than Zinnat# with the mean (90% CI) of difference in Tmax of -0.5 [(-1.01)-0.01] h. Bioequivalence analysis showed that the AUC 0-∞ and the Cmax of the two products were not significantly different. The point estimator (90% CI) for the ratio [Furoxime®/Zinnat®] of log transformed data of the Auc 0-∞ and Cmax were 1.03 (0.98-1.20) and 1.09 (1.02-1,24), respectively and were within the bioequivalence range of 0.80-1.25.